Gardener-associated fibroma: an unusual cause of upper airway obstruction. (28th September 2018) - Pinto, Rohan Sebastian; Simons, Anthony; Verma, Rohit; Bateman, Neil
Abstract : We present the first case of upper airway obstruction secondary to a retropharyngeal Gardner-associated fibroma (GAF). A 16-month-old infant presented with a 3-month history of worsening dyspnoea and apnoeic episodes. Examination revealed stridor and left-sided retropharyngeal asymmetry. MRI demonstrated a mass in the retropharynx. Tracheostomy and pharyngeal biopsy under anaesthesia were performed, and histology confirmed a diagnosis of GAF. The mass was excised using a transcervical approach, and postoperative recovery was unremarkable. GAF is associated with Gardner's syndrome (GS) and familial adenomatous polyposis (FAP), both of which are associated with multiple colonic polyps and increased risk of colorectal malignancy. Subsequent testing for an APC mutation seen in GS and FAP was negative in our patient. The details of this unusual presentation of a rare disease are given in addition to a review of the literature.